DEPICTION OF FEMINISM CONCEPT IN DISNEY ANIMATED MOVIE: ENCANTO 2021 - Salamina, Lugina Ayu; Tawami, Tatan (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2023)
This paper is entitled "Depiction of feminism concept in Disney animated movie: Encanto 2021". The goal of this paper is to describe how the concept of Feminism is portrayed and which feminisms appear in the Disney animated film Encanto. As a result, the concept of Feminism is the object of this research. In this regard, the data used in this study are those related to the concept of feminism, and they are taken from a conversation between characters in the film. The movie script transcription is used to qualify this study in addition to the conversation transcription. The qualitative-descriptive method is used to describe data and analysis in a structured manner. The qualitative research method is used to generate descriptive data in the form of sentences and paragraphs. Based on the analysis, Encanto’s women characters are identified as independent woman and has a several feminism values in themselves, such as liberal feminism value, ecofeminism value, and also socialist feminism value. Keywords: Animated movie, Encanto, Feminism